PEMBERDAYAAN DAN PENDAMPINGAN ANAK MIGRAN INDONESIA MELALUI PROGRAM KKN INTERNASIONAL DI SELANGOR, MALAYSIA - Sukma, Tiara; Kurniadi, Didit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian migrant children in Selangor, Malaysia, still face limited access to education, literacy, basic healthcare, as well as character and religious development. These conditions form the basis for the implementation of the “Mangunsari Goes Abroad 2026” International Community Service Program (KKNI) at the Elshaddai Learning Center (SB) under the auspices of the Indonesian School of Kuala Lumpur, Malaysia. This article aims to describe the implementation and evaluate the achievements of the International Community Service Program in empowering Indonesian migrant children through six areas of service: education, health, entrepreneurship, the environment, tourism, and religious education. The program involved 55 elementary school students as participants. Data were collected through observation, documentation, and hands on practice and demonstrations and were then analyzed descriptively to illustrate the program’s achievements in each area of activity. The results showed an increase in participants’ engagement in literacy activities, interest in reading and writing, ability to practice clean and healthy living habits, creativity in simple entrepreneurship, ability to sort waste, appreciation for Indonesian tourist destinations, as well as the ability to memorize prayers, read the Qur’an, and learn basic Arabic in accordance with the participants’ developmental levels. All participants demonstrated high levels of engagement and enthusiasm throughout the program. Overall, the implementation of the International Community Service Program made a positive contribution to improving literacy, clean and healthy living habits, creativity, environmental awareness, national identity, and religious understanding among Indonesian migrant children, while also strengthening Indonesia’s national identity and cultural diplomacy abroad.